Lofgren’s syndrome, a presentation of Sarcoidosis: A Case report - Shrestha, Samrat; Ranjit, Sudina (Journal of Advances in Internal Medicine, 2025)
Sarcoidosis, a granulomatous disorder of unknown cause, is an autoimmune multisystem condition that primarily impacts adults between the ages of 20 and 40. While the condition can affect nearly any organ in the body, it typically manifests as pulmonary infiltrates, skin lesions, eye issues, and joint problems. Lofgren's syndrome, characterized by acute arthritis, erythema nodosum, and bilateral hilar lymphadenopathy, is an unusual initial presentation of sarcoidosis. . We describe here a newly diagnosed case of sarcoidosis that presented as Lofgren’s syndrome. Acute sarcoid arthritis should be kept as one of differential diagnosis for patient presenting with acute arthritis and skin lesions. Chest X Ray should be considered to rule out bilateral hilar lymphadenopathy. Early suspicion and recognition of typical features are crucial for making a diagnosis.